Statistical Study of The Sphere of Trade in The Russian Federation ("Journal "U". Economy. Management. Finance.", 2021)
The article presents an analysis of changes in the main statistical indicators of the sphere of trade in Russia for 2005-2020. Such indicators as the number of enterprises in the sphere of trade, the dynamics of retail and wholesale turnover are considered. Conclusions are drawn about the importance of the sphere of trade in the modern economy of the country.
Keywords: trade; retail turnover; wholesale turnover; trading enterprises; consumption